Framing Kata ‘Etika’ pada Pemberitaan Debat Capres 2024 di Metrotvnews.com dan Republika.co.id - Adevy Vanie; Zulpikri Rangkuti (MUKASI: Jurnal Ilmu Komunikasi, 2024)
The purpose of this research is to understand the framing of the word “Ethics” used by Anies Rasyid Baswedan in the coverage of the third and fourth presidential candidate debates in the online media Metrotvnews.com and Republika.co.id in 2024. This research uses a qualitative approach with Murray Edelman's framing analysis method, which is an analysis of categorization, miscategorization, rubrication and ideological categorization. Data collection uses primary data in the form of research and documents and secondary data obtained through selected information as data obtained from books, scientific articles. The results of this study show that the online media Metrotvnews.com accentuates Anies Rasyid Baswedan as a leader who is critical of Prabowo Subianto's ethics so that it can form a positive image in the eyes of the public, while the online media Republika.co.id accentuates criticism of Anies from the chairman of the PAN DPR faction Saleh Partaonan Daulay, framing Anies regarding his inconsistency in talking about ethics. Because according to Saleh, Anies is a person who talks about ethics but does not show ethics in his actions.